Multifield‐Inspired Tunable Carrier Effects Based on Ferroelectric‐Silicon PN Heterojunction. (18th November 2019) - Lou, Jing; Ma, Hua; Wang, Jun; Yang, Ruisheng; Dong, Bowen; Yu, Ying; Wang, Jiafu; Zhang, Fuli; Fan, Yuancheng; Feng, Mingde; Li, Zhiqiang; Nan, Cewen; et al.
Abstract: Tuning the carrier behavior in a heterostructure is important for designing well‐performing electro‐optical devices. Scientific research has mainly focused on 2D and layered materials due to their high carrier mobility. Ferroelectrics exhibit a strong response to external fields and are widely employed in microwave and terahertz (THz) tunable devices. By constructing a ferroelectric‐silicon PN heterojunction, a new strategy is proposed to construct a nonequilibrium carrier layer and achieve tunable carrier effects under multifield coupling. Theoretically, the formation of a carrier layer based on the interaction between free carriers and bound surface charges is analyzed, and a design method for PN heterojunction engineering is presented. Experimentally, a PN heterojunction of Ba0.7 Sr0.3 TiO3 thin film on silicon substrate is constructed, and three tunable carrier effects are achieved. A broadband tunable THz modulator with an amplitude modulation depth of 99.5% is realized, which is superior to other works. The volt–ampere effect of the PN heterojunction can be dynamically adjusted. The shape of the hysteresis loops can be dynamically controlled in real time. This proposed strategy for carrier modulation is a giant step forward in ferroelectrics applications and a path for the development of electro‐optical applications with new materials. Abstract : By depositing Ba0.7 Sr0.3 TiO3 thin film on silicon, a new strategy is proposed to construct a nonequilibrium carrier layer and achieve tunable carrier effects under multifield coupling. The modulation depth of terahertz waves by nonequilibrium carrier layer reaches 99.5%. The dynamic tunability of volt–ampere curves and hysteresis loops reveals the featured characteristics of PN heterojunction.